2002
DOI: 10.1038/sj/pcan/4500553
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related peptide: expression in prostate cancer bone metastases

Abstract: Parathyroid hormone-related peptide (PTHrP) is a regulatory protein associated with cell growth in non-osseous tissues and with osteoclast stimulation in bone. It has been implicated in the pathogenesis of bone metastases, particularly in breast carcinoma. PTHrP is widely expressed in primary prostate cancers, but there are few reports of its expression in prostatic metastases. The aim of this study was to examine the expression of PTHrP in bone metastases from patients with untreated adenocarcinoma of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…npg vascular endothelial growth factor, platelet-derived growth factor and MDA-BF [77]. A further interesting aspect of the cytokine balance in PCa metastasis relates to the IGF axis and parathyroid hor mone-related protein (PTHrP), which is produced in PCa bone metastases [78]. The prostate-specific antigen (PSA), a known protease, cleaves PTHrP and possibly shifts the balance within the immediate milieu of the prostate metastasis from bone resorption to formation [79,80].…”
Section: Molecular Mechanisms Of Metastatic Prostate Cancer In the Bomentioning
confidence: 99%
See 1 more Smart Citation
“…npg vascular endothelial growth factor, platelet-derived growth factor and MDA-BF [77]. A further interesting aspect of the cytokine balance in PCa metastasis relates to the IGF axis and parathyroid hor mone-related protein (PTHrP), which is produced in PCa bone metastases [78]. The prostate-specific antigen (PSA), a known protease, cleaves PTHrP and possibly shifts the balance within the immediate milieu of the prostate metastasis from bone resorption to formation [79,80].…”
Section: Molecular Mechanisms Of Metastatic Prostate Cancer In the Bomentioning
confidence: 99%
“…However, when PTHrP is present (as in murine osteoblasts and haemopoietic progenitors in culture [92]), osteoclasts differentiate in the absence of other stimulatory agents, suggesting that PTHrP plays a facilitating role. PTHrP is a major factor in bone resorption in breast cancer [93] and is expressed in both primary tumours and bone metastases of PCa [78].…”
Section: Molecular Mechanisms Of Metastatic Prostate Cancer In the Bomentioning
confidence: 99%
“…In the corresponding bone metastases, all 14 were positively staining, all but three being uniformly stained. Previous studies of 10 (Bryden et al, 2002) and 14 (Iddon et al, 2000) archival prostatic bone metastases by immunohistochemistry have demonstrated PTHrP expression in only 50% of samples. Differences in the technique of PTHrP detection are unlikely to account for this, as concordance between immunohistochemistry and in-situ hybridization for detection of PTHrP has been described (Iwamura et al, 1994b) suggesting that PTHrP expression is regulated at the gene level.…”
Section: Discussionmentioning
confidence: 99%
“…Work in breast carcinoma has suggested that PTHrP may be an important factor in bone metastasis. Serum PTHrP levels are elevated in patients with bone metastases (Bundred et al, 1991) and that there is up regulation of PTHrP expression in the metastatic tissue (Powell et al, 1991). Additionally there are also found to be high levels of expression of the receptor for PTHrP in breast cancer bone metastases (Downey et al, 1996).…”
mentioning
confidence: 99%
“…These sections were previously identified as prostatic bone marrow metastases by positive PSA staining (Bryden et al, 2002). Figure 2 shows immunohistochemical (DAB) staining for MMP-1, MMP-7 and uPA using the same concentration of antibody as for the co-culture staining.…”
Section: Enzyme Characterisation Of Bone Marrow Metastasesmentioning
confidence: 99%